2017
DOI: 10.14201/fjc201715199217
|View full text |Cite
|
Sign up to set email alerts
|

¿Digo lo que siento y siento lo que digo? Una aproximación transcultural al uso de los emoticonos y emojis en los mensajes en CMC

Abstract: RESUMENEl uso de los emojis y emoticonos entre los usuarios de mensajería online es un fenómeno global y generalizado. El presente estudio analiza las preferencias entre los usuarios de unos emojis y emoticonos sobre otros con el fin de adecuar mejor la expresión de sus mensajes con la emoción que contienen. Lo hacen así para intensificar o difuminar la rigidez textual. También, para manifestar su propia empatía durante las interacciones del proceso comunicativo. Este trabajo analiza el uso de estos símbolos y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 22 publications
2
4
0
3
Order By: Relevance
“…It is in this way that ideograms have the potential to manage and even improve interpersonal relationships and promote positive interactions in the setting of text messaging as the de facto alternative to voice-based communication . In fact, ideograms in our study tended to be used to convey positive rather than negative affect, affirming the results from another study . Our findings also echo those of a focus group on user experiences with clinical texting.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is in this way that ideograms have the potential to manage and even improve interpersonal relationships and promote positive interactions in the setting of text messaging as the de facto alternative to voice-based communication . In fact, ideograms in our study tended to be used to convey positive rather than negative affect, affirming the results from another study . Our findings also echo those of a focus group on user experiences with clinical texting.…”
Section: Discussionsupporting
confidence: 86%
“… 20 , 25 , 26 In fact, ideograms in our study tended to be used to convey positive rather than negative affect, affirming the results from another study. 27 Our findings also echo those of a focus group on user experiences with clinical texting. In that study, Lee and colleagues 24 discovered that while some users complained about the use of emoji in texts from nurses, others defended it as a way of conveying positive affect.…”
Section: Discussionsupporting
confidence: 81%
“…In terms of usage behavior, following Hofstede's cultural dimension model, people in countries with high power distance and indulgence use more emoji representing negative emotions, while people in countries with high uncertainty avoidance, individualism and long-term orientation often use emoji representing positive emotions (Xuan et al, 2016). Specifically, Chinese users are more likely than Spanish users to use non-verbal cues such as emoji and emoticons to express negative emotions (Cheng, 2017). Research has also found that people from Hong Kong and the US use emoji differently on user-generated restaurant reviews websites, which may reflect underlying cultural differences (Chik and Vasquez, 2017).…”
Section: The Use Of Emojimentioning
confidence: 99%
“…Because of their rich emotional meanings, emoji are often used to express emotions in online communication. In general, users tend to use emoji in positive messages and to use them less in sad or angry messages (Cheng, 2017). Different emoji affect people's attention and responses in divergent ways (Hjartstrom et al, 2019).…”
Section: Functions Of Emojimentioning
confidence: 99%
“…De hecho, investigaciones han demostrado que estas señales pueden ser igual de eficaces que el lenguaje no verbal regular (Fadhli-Wibowo et al, 2017). Por lo tanto, estas pueden ayudar a aclarar los mensajes (Wang et al, 2014) y proporcionar información sobre el tipo y la fuerza de las emociones que el remitente desea transmitir (Cheng, 2017), así como la fuerza ilocucionaria de los mensajes (Diehl, 2018;Ernst & Huschens, 2018). Incluso, una investigación en neurociencias demostró que los emojis de cara alegre se asocian a nivel cortical con expresiones faciales de las personas, lo que "retroalimenta al sujeto favoreciendo el contagio emocional y, finalmente, la respuesta de empatía afectiva" (Gantiva et al, 2019, p.14).…”
unclassified